Specific leaf area response of Panicum coloratum L. with different defoliation management (Semiárida, 2021)
The objective was to evaluate the response of the specific leaf area (AFE) to different combinations of cutting interval (IC) and cutting height (AC) on tillers cohorts (Co) of Panicum coloratum L. The work was carried out from SeptemberMarch, in greenhouse, on 81 plants grown in PVC pots and distributed in a DCA with factorial arrangement of treatments and repeated measures. The treatments included nine replications of the possible combinations between the IC of 2, 4 and 6 leaves.tiller1 and the AC of 40, 80 and 120 mm for seven cohorts of tillers. In each cut, three tillers were randomly selected per cohort and repetition in which the leaf area (AF) of the penultimate expanded leaf was determined; the leaf blade were dried and weighed to determine their weight (PF)and calculate the AFE. The data were analyzed using ANOVA and the slope and intercept of the relationship between (log10) PF and (log10) AF were estimated, with dummy variables to establish differences between the IC. The variation in AFE as a function of IC was different according to AC (IC×AC interaction; p
Keywords: C4 grass; defoliation interval; defoliation height; phenotypic plasticity; tolerance to grazing